Manajemen Sumber Daya Manusia Dalam Meningkatkan Pelayanan Pada Cafe Aceh Meutuah Khupie Tembung - Maulida, Syakya; Ramadhani, Sri (Universitas Labuhanbatu, 2024)
The purpose of this study is to determine the effect of the quality of human resources on service improvement. The research method used in this study is a qualitative descriptive method, namely a research method that uses qualitative data and described descriptively. The results of the study show that (1) at Cafe Aceh Meutuah Khupie there is no shortage of human resource management to improve service, but the deficiencies are caused by the owner's decision to follow the goal of opening a new cafe branch. (2) The sales promotion carried out by Cafe Aceh Meutuah Khupie is only based on word of mouth from customers and does not carry out other sales promotions. (3) Service quality has a significant effect on customer loyalty. (4) Consumer satisfaction moderates (weakens) the influence of consumer quality. (5) Cafe atmosphere has a big effect on customer loyalty.Researchers can give to UMKM are to provide SOP (standard operating procedures) to employees so that employees and production trips can produce maximum products.